Advancing social media derived information messaging and management: A multi-mode development perspective. (April 2020) - Martin, Nigel; Rice, John; Arthur, Damien
Graphical abstract: Highlights: The research developed a four mode taxonomy for SM development. A group of project managers recommended a development mode for six diverse firms. The functional development mode was recommended as suitable for multiple firms. Firms can employ focused development modes for 'listen and learn' programs. Groundswell promotions can be integrated with SM best practice and multi-organizational collaborations. Abstract: With global reach of over 2 billion active users, the evolution of Social Media (SM) systems has provided organizations with sophisticated tools and technologies for delivering business objectives. Importantly, while marketers and public relations experts have taken leading positions in promotion and advancement of SM, project managers are often tasked with delivering SM systems. In this study, a sample of 127 project managers were asked to evaluate and recommend modes of SM development for six diverse firms using a four-part taxonomy. The results show that firms of varying size can employ narrowly focused and low cost SM development modes to meet their business objectives, with well-resourced firms able to use experimental modes to deliver widespread and higher cost 'listen and learn' SM systems. Alternatively, in addition to achieving groundswell promotions and broader business marketing and sales influencing objectives, firms that engage in large scale SM developments can document and implement SM best practices and apply multi-organizational collaborations required for information exchange, customer feedback and experience sharing. These managerial perspectives expose the intrinsic connections between SM systems and information messaging and management within firms. The article builds further into cumulative studies directed at SM systems construction, deployment, and firm capability affordances.